In vitro comparison of the cariostatic effect between topical application of fluoride gels and fluoride toothpaste Comparação in vitro do efeito cariostático entre a aplicação tópica de flúor e dentifrício fluoretado - Alberto Carlos Botazzo Delbem; Fernanda Lourenção Brighenti; Ana Elisa de Mello Vieira; Jaime Aparecido Cury (University of São Paulo, 2004)
The aim of this study was to compare the effect of topical fluoride products [acidulated phosphate fluoride (APF) or neutral gel (NF) x fluoride toothpaste (MFP)], in respect to fluoride uptake and anticariogenic action. One hundred and twenty five blocks of human teeth, sorted in 5 groups according to the treatment, were submitted to pH cycling for ten days. The parameters analyzed were: fluoride uptake before and after pH cycling and surface (SMH) and cross-sectional (CSMH) microhardness of the enamel blocks. The results of fluoride concentration in enamel after the pH cycling showed an enhancement of fluoride uptake for all groups compared to sound control. No significant differences between APF and MFP were observed for surface microhardness, percentage change of surface microhardness and mineral loss. The volume percent mineral obtained from cross-sectional microhardness demonstrated that APF has a different lesion progression rate regarding subsurface carious lesion. The results suggest that professionally applied fluoride gel or frequent fluoride application in low concentration is a positive preventive measure for the control of dental caries. O objetivo do presente estudo foi comparar in vitro o efeito da aplicação tópica de flúor na forma de gel acidulado (FFA) ou neutro (FFN) com um dentifrício fluoretado (MFP), na incorporação e ação anticariogênica do flúor. Foram utilizados 125 blocos obtidos de esmalte humano, divididos em 5 grupos de acordo com o tratamento e submetidos à ciclagem de pH durante dez dias. Analisou-se o flúor incorporado antes e depois da ciclagem de pH; a microdureza superficial (SMH) e a microdureza interna do esmalte (CSMH). Os resultados da concentração de flúor no esmalte após a ciclagem indicou uma maior quantidade de flúor incorporado para todos os grupos comparados ao grupo controle sadio. A microdureza superficial entre APF e MFP, assim como a porcentagem de alteração da microdureza superficial e a perda mineral não mostraram diferenças estatísticas. A porcentagem de volume mineral obtida a partir da microdureza em secção longitudinal demonstrou que o APF tem um padrão melhor na formação da cárie subsuperficial. Os resultados sugerem que o uso de géis acidulados ou a freqüente aplicação de flúor em baixa concentração são medidas eficazes para o controle da cárie dental.